A process for rapid hydration of anhydrous gypsum

By using technical means such as sulfate hydrating agents and composite surfactants in the hydration process of anhydrous salt gypsum, the problems of high cost and low hydration rate of anhydrous salt gypsum are solved, and efficient and low-cost hydration effect is achieved.

CN119059750BActive Publication Date: 2025-03-21JIANGSU EFFUL SCIENCE AND TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411571792.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing anhydrous salt gypsum hydration process is high and the hydration rate is low. The increase in the amount of exciter added may lead to a decrease in the strength of dihydrated gypsum, affecting the quality and hydration rate.

Method used

Sulfate hydration promoters (such as calcined alum) are used to combine dihydrate gypsum seed crystals, composite surfactants and water reducing agents, and optimized through grinding and stirring to improve the hydration rate and hydration rate of anhydrous salt gypsum.

Benefits of technology

The low-cost and rapid hydration of anhydrous salt gypsum is achieved, ensuring the high strength and stability of dihydrate gypsum, and improving the economical and environmental protection of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of cement and provides a process for rapid hydration of anhydrous gypsum, comprising the following steps: S1, grinding the anhydrous gypsum to a specific surface area of ​​480-520m 2 / kg, powdered anhydrous salt gypsum is obtained for standby use; S2, the powdered anhydrous salt gypsum, dihydrate gypsum seed, hydration promoter, composite surfactant, water reducer and deionized water of step S1 are mixed, stirred at 15-25 ° C for 23-25h, and a hydrated slurry is obtained for standby use, wherein the composite surfactant is a mixture of modified lignin-based surfactant and tristyrylphenol polyoxyethylene ether phosphate monoester; S3, anhydrous ethanol is added to the hydrated slurry of step S2, filtered, washed, and dried to constant weight to obtain dihydrate gypsum. The anhydrous salt gypsum hydration process provided by the present invention has the characteristics of low cost and high hydration rate, and has good commercial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cement, and in particular to a process for rapid hydration of anhydrous salt gypsum. Background Art

[0002] The main component of salt gypsum is anhydrous gypsum, that is, anhydrous salt gypsum, which cannot be directly processed into building materials. Factories can only use it for road construction mortar, cement additives, etc. It has a narrow market sales channel and low added value, and the factory is under great environmental pressure. However, this salt gypsum also has advantages, such as whiteness greater than 85%, few impurities, uniform crystal particles, and no radioactive substances. Therefore, in industry, anhydrous salt gypsum is often converted into dihydrate gypsum through hydration process.

[0003] However, due to the low solubility and hydration rate of anhydrous gypsum, it is very difficult to dissolve and transform it into dihydrate gypsum directly and quickly. For industrial production and application, the grade of dihydrate gypsum must reach more than 90%, and the hydration completion time must be controlled within 48 hours. Otherwise, it will not be economical due to the large capacity of the hydration tank, large land occupation and high investment. Therefore, in order to increase the hydration rate of anhydrous gypsum, people have developed various stimulants, i.e., hydration promoters, such as sulfates, non-sulfate salts, inorganic materials, etc. Among them, sulfate stimulants have better promoting effects and are more mature in application, but there is still a problem that increased addition may lead to a decrease in the strength of dihydrate gypsum and thus a decrease in quality and hydration rate.

[0004] Patent CN 110128045 A discloses an activator for rapid hydration of type II anhydrous gypsum and a rapid hydration method. The activator used in the application includes an active activator, dihydrate gypsum seeds and an aqueous solution, wherein the active activator includes one or more of potassium aluminum sulfate dodecahydrate, sodium hydrogen sulfate, potassium dichromate, sodium oxalate, and calcined alum. It has the advantages of energy saving, environmental protection, and rapid hydration, but does not solve the problem that the strength of dihydrate gypsum decreases due to an increase in the amount of activator added, thereby reducing the quality and hydration rate.

[0005] Therefore, there is an urgent need in the market for a low-cost, high-hydration-rate process for the rapid hydration of anhydrous gypsum. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention selects sulfate hydration promoters to promote the hydration of anhydrous gypsum as the basis, adds dihydrate gypsum seeds, composite surfactants and water reducers, and optimizes the hydration method and conditions, thereby solving the problems of high cost and low hydration rate in the anhydrous gypsum hydration process.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides a process for rapid hydration of anhydrous gypsum, comprising the following steps:

[0009] S1. Grind the anhydrous gypsum to a specific surface area of ​​480-520m 2 / kg, obtain powdered anhydrous salt gypsum for use;

[0010] S2, mixing the powdered anhydrous salt gypsum, dihydrate gypsum seed, hydration promoter, composite surfactant, water reducer and deionized water of step S1, stirring at 15-25° C. for 23-25 ​​hours to obtain a hydrated slurry for standby use, wherein the composite surfactant is a mixture of modified lignin-based surfactant and tristyrylphenol polyoxyethylene ether phosphate monoester;

[0011] S3. Add anhydrous ethanol to the hydrated slurry in step S2, filter, wash, and dry to constant weight to obtain dihydrate gypsum.

[0012] In some embodiments of the present invention, the mass ratio of the powdered anhydrous gypsum to the dihydrate gypsum seed crystals in step S2 is 1:(0.15-0.25).

[0013] Preferably, in step S2, the mass ratio of the powdered anhydrous gypsum to the dihydrate gypsum seed crystals is 1:0.2.

[0014] In some embodiments of the present invention, the powdered anhydrous salt gypsum, hydration promoter, composite surface

[0015] The mass ratio of active agent to water reducing agent is 1: (0.04-0.06): (0.003-0.005): (0.001-0.0014).

[0016] Preferably, the powdered anhydrous salt gypsum, hydration promoter, composite surfactant and water reducing agent in step S2 are of

[0017] The quantitative ratio is 1:0.05:0.004:0.0012.

[0018] In some embodiments of the present invention, the hydration promoting agent in step S2 is calcined alum.

[0019] In some embodiments of the present invention, the mass ratio of the modified lignin-based surfactant to tristyrylphenol polyoxyethylene ether phosphate monoester in the composite surfactant in step S2 is 1:(0.08-0.12).

[0020] Preferably, the mass ratio of the modified lignin-based surfactant to tristyrylphenol polyoxyethylene ether phosphate monoester in the composite surfactant in step S2 is 1:0.1.

[0021] In some embodiments of the present invention, the method for preparing the modified lignin-based surfactant in step S2 comprises the following steps:

[0022] (1) Add sodium lignin sulfonate to deionized water, introduce inert gas, heat to 45-55°C, stir for 15-25 minutes, add potassium persulfate, stir for 20-40 minutes, heat to 70-80°C, add methyl allyl polyoxyethylene ether, stir for 3-4 hours, add isopropanol, purify, dry, grind, and obtain the product for use;

[0023] (2) Add the product of step (1) into deionized water, add sodium hydroxide aqueous solution to adjust the pH to 10-12, add N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, stir at 65-75° C. for 10-20 min, add formaldehyde aqueous solution, heat to 80-90° C., react for 3-4 h, cool to room temperature, add anhydrous ethanol, take the solid, wash, and dry to obtain a modified lignin-based surfactant.

[0024] In some embodiments of the present invention, in step (1), the mass ratio of sodium lignin sulfonate to methyl allyl polyoxyethylene ether is 1:(0.5-0.7).

[0025] Preferably, in step (1), the mass ratio of sodium lignin sulfonate to methyl allyl polyoxyethylene ether is 1:0.6.

[0026] In some embodiments of the present invention, in step (2), the mass ratio of the product to N-butyl-2,2,6,6-tetramethyl-4-piperidinamine is 1:(0.1-0.3).

[0027] Preferably, in step (2), the mass ratio of the product to N-butyl-2,2,6,6-tetramethyl-4-piperidinamine is 1:0.2.

[0028] In some embodiments of the present invention, the water reducing agent is a melamine-based water reducing agent.

[0029] The applicant adopts a combination of physical excitation and chemical excitation to promote the hydration reaction, wherein grinding causes the dense structure of natural anhydrous gypsum to be destroyed to a certain extent, the specific surface area is increased, the hydration effect is enhanced, and the specific surface area of ​​the anhydrous gypsum after grinding is controlled to have the best hydration rate; calcined alum is selected as a hydration promoter for chemical excitation, which shortens the setting time of gypsum, changes the crystal morphology of the hydration product, increases the aspect ratio of the crystal, improves the strength and water resistance of the hardened body, and significantly improves the hydration rate of the anhydrous gypsum.

[0030] Furthermore, the applicant uses calcined alum as a hydration promoter, which provides a large amount of SO4 2- , K + and Al 3+ , SO4 2-The rapid increase in concentration breaks the dissolution balance of anhydrous gypsum. At this time, SO4 2- Ca dissolved from anhydrous gypsum 2+ Combined with water molecules to form dihydrate gypsum, on the one hand, the dissolved Ca 2+ is consumed in large quantities, and Ca 2+ The concentration of Al decreases, which continues to promote the dissolution of anhydrous gypsum, thereby promoting the formation of dihydrate gypsum and increasing the speed of hydration. 3+ It is easily hydrolyzed in water, making the system acidic, thereby making anhydrous gypsum more soluble, further promoting the hydration process; and after calcining alum, the conflict with the water reducer is avoided, ensuring the effect of the hydration promoter and the water reducer on the anhydrous gypsum to stimulate and increase the fluidity; further, there is a cross-linking effect between the sulfonate group in the modified lignin-based surfactant and the amine group in the melamine-based water reducer, making the hydration system more stable and promoting the improvement of the hydration rate.

[0031] Although calcined alum has the above-mentioned excellent characteristics as a hydration promoter, as the amount of calcined alum added gradually increases, the flexural and compressive strengths of dihydrate gypsum may tend to increase first and then decrease. The applicant controls the amount of calcined alum added and also uses it in combination with a surfactant. After the addition of the surfactant, the absolute value of the zata potential of the solution system is significantly increased, so that the dihydrate gypsum forms a denser structure as a whole, ensuring the stability of the flexural and compressive strengths of the dihydrate gypsum. In addition, the surfactant can also make the dispersion of gypsum particles more uniform and stable, which is beneficial to improving the hydration rate and plays a role in jointly stimulating the hydration of anhydrous gypsum.

[0032] Sodium lignin sulfonate is a high-molecular anionic surfactant. Its molecular structure contains a phenylpropane hydrophobic skeleton as well as hydrophilic groups such as sulfonic acid, alcohol hydroxyl, and carboxyl. It has a certain dispersing ability, and the sulfonate group is an active group, which can easily adsorb with the active sites on the surface of anhydrous gypsum to form a dense adsorption layer, thereby increasing the electrostatic repulsion and achieving the purpose of uniform dispersion of anhydrous gypsum particles. However, due to its low surface activity, its dispersion performance is not ideal, resulting in its application generally at a low level.

[0033] On the one hand, the applicant uses methyl allyl polyoxyethylene ether having multiple polyethylene glycol hydrophilic chains to modify sodium lignin sulfonate to obtain a product, thereby improving the hydrophilicity of sodium lignin sulfonate and thus improving its dispersibility. In addition, multiple polyoxyethylene ether structural units significantly increase the molecular weight of the modified lignin-based surfactant, which has good stability and is conducive to its extension and dispersion in the system. On the other hand, the applicant introduces N-butyl-2,2,6,6-tetramethyl-4-piperidinamine to modify the product. Piperidinamine has high stability and good antioxidant properties, which is conducive to maintaining the stability of the modified lignin-based surfactant. In addition, the diamine group in the structure of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine has a certain hydrophilicity, which can improve the dispersibility of the modified lignin-based surfactant to a certain extent.

[0034] However, the introduction of secondary amine groups in N-butyl-2,2,6,6-tetramethyl-4-piperidinamine may weaken the electrostatic repulsion between modified lignin-based surfactants, thereby forming large-particle aggregates. Furthermore, the applicant compounded tristyrylphenol polyoxyethylene ether phosphate monoester with modified lignin-based surfactants as a composite surfactant, which can inhibit the aggregation behavior of modified lignin-based surfactants in water and has a good dispersing and stabilizing effect on the aggregates; further, there is a certain cross-linking effect between the -C=C- in tristyrylphenol polyoxyethylene ether phosphate monoester and the -C=C- in methyl allyl polyoxyethylene ether, which can make the composite surfactant more stable.

[0035] In some embodiments of the present invention, the hydration rate of the process for rapid hydration of anhydrous gypsum described in the above technical solution is not less than 93%.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention provides a process for the rapid hydration of anhydrous gypsum, which is based on the use of sulfate hydration promoters to promote the hydration of anhydrous gypsum, adding dihydrate gypsum seeds, composite surfactants and water reducers, and optimizing the hydration method conditions, so that the process for the hydration of anhydrous gypsum has the characteristics of low cost and high hydration rate.

[0038] (2) The present invention adopts calcined alum as a hydration promoter, which ensures a good hydration stimulating effect while avoiding the conflict with the water reducer. The synergistic effect between the systems ensures that the hydration promoter and the water reducer can stimulate and increase the fluidity of anhydrous gypsum.

[0039] (3) The present invention uses a hydration promoter and a surfactant in combination. After the surfactant is added, the absolute value of the zata potential of the solution system is significantly increased, and the dispersion of the gypsum particles is more uniform and stable, which plays a role in jointly stimulating the hydration of anhydrous gypsum and improving the hydration rate.

[0040] (4) The present invention prepares a modified lignin-based surfactant, wherein sodium lignin sulfonate is modified by using methyl allyl polyoxyethylene ether and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, and compounded with tristyrylphenol polyoxyethylene ether phosphate monoester to obtain a composite surfactant, which has good dispersibility and stabilization effects and effectively improves the hydration rate.

[0041] (5) The process for rapid hydration of anhydrous gypsum of the present invention has a hydration rate of not less than 93%. DETAILED DESCRIPTION

[0042] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0043] In the following examples, except for the modified lignin-based surfactant, the other compound monomers and related reagents used can be purchased from the market, among which anhydrous salt gypsum, i.e. anhydrous gypsum, was purchased from Zaozhuang Xinghao New Materials Co., Ltd.; calcined alum was purchased from Guzhen Mineral Products Co., Ltd., Lujiang County, Anhui Province; methyl allyl polyoxyethylene ether was purchased from Pandex (Shanghai) International Trade Co., Ltd.; tristyrylphenol polyoxyethylene ether phosphate monoester was purchased from Hai'an Petrochemical Plant, Jiangsu Province; the model of melamine-based water reducer was F10, which was purchased from Shanghai Hengchuang Chemical Co., Ltd.

[0044] Preparation Example 1

[0045] The synthesis method of the modified lignin-based surfactant A comprises the following steps:

[0046] (1) Add 30 g of sodium lignin sulfonate to 100 ml of deionized water, introduce N2, heat to 50 ° C, stir for 20 min, add 0.12 g of potassium persulfate, stir for 30 min, heat to 75 ° C, add 18 g of methyl allyl polyoxyethylene ether, stir for 3.5 h, add 2 ml of isopropanol, purify (cool to room temperature, add 200 ml of isopropanol, stir for 30 min, let stand for 4 h, take the lower layer of liquid, filter, add 80 ml of anhydrous ethanol, stir for 30 min, let stand for 30 min, filter, take the precipitate, add 120 ml of anhydrous methanol, stir for 30 min, filter, take the precipitate, use acetone as the extractant, Soxhlet extraction for 5 h), dry at 80 ° C and -0.1 MPa for 24 h, grind for 5 min, and obtain the product for use;

[0047] (2) 10 g of the product of step (1) was added to 50 ml of deionized water, 30 wt % sodium hydroxide aqueous solution was added dropwise to adjust the pH to 11, 2 g of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine was added, and the mixture was stirred at 70 ° C for 15 min. 12 ml of 10 wt % formaldehyde aqueous solution was added, the mixture was heated to 85 ° C, and the reaction was carried out for 3.5 h. The mixture was cooled to room temperature, 200 ml of anhydrous ethanol was added, the solid was taken, washed with anhydrous ethanol for 3 times, and dried at 45 ° C for 24 h to obtain a modified lignin-based surfactant A.

[0048] Preparation Example 2

[0049] The specific implementation manner of the modified lignin-based surfactant B is the same as that of the modified lignin-based surfactant A, except that in step (1), the mass of methyl allyl polyoxyethylene ether is replaced with 12 g.

[0050] Preparation Example 3

[0051] The specific implementation manner of the modified lignin-based surfactant C is the same as that of the modified lignin-based surfactant A, except that in step (2), the mass of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine is replaced with 0.5 g.

[0052] Example 1

[0053] A process for rapid hydration of anhydrous gypsum comprises the following steps:

[0054] S1. Grind 50g of anhydrous gypsum to a specific surface area of ​​500m 2 / kg, obtain powdered anhydrous salt gypsum for use;

[0055] S2, 30g of the powdered anhydrous gypsum of step S1, 6g of dihydrate gypsum seed, 1.5g of calcined alum, 0.12g of composite surfactant, 0.036g of melamine-based water reducer and 200ml of deionized water were mixed, and stirred at 20°C for 24h to obtain a hydrated slurry for standby use, wherein the composite surfactant is a mixture of modified lignin-based surfactant A and tristyrylphenol polyoxyethylene ether phosphate monoester, and the mass ratio is 1:0.1;

[0056] S3. Add 50 ml of anhydrous ethanol to the hydrated slurry in step S2, filter with suction, wash with anhydrous ethanol three times, dry at 45° C. to constant weight, measure the content of crystal water, and calculate the corresponding hydration rate.

[0057] Example 2

[0058] A process for rapid hydration of anhydrous gypsum comprises the following steps:

[0059] S1. Grind 50g of anhydrous gypsum to a specific surface area of ​​480m 2 / kg, obtain powdered anhydrous salt gypsum for use;

[0060] S2, 30g of the powdered anhydrous gypsum of step S1, 4.5g of dihydrate gypsum seed, 1.2g of calcined alum, 0.09g of composite surfactant, 0.03g of melamine-based water reducer and 200ml of deionized water were mixed, and stirred at 15°C for 25h to obtain a hydrated slurry for standby use, wherein the composite surfactant is a mixture of modified lignin-based surfactant A and tristyrylphenol polyoxyethylene ether phosphate monoester, and the mass ratio is 1:0.08;

[0061] S3. Add 50 ml of anhydrous ethanol to the hydrated slurry in step S2, filter with suction, wash with anhydrous ethanol three times, dry at 45° C. to constant weight, measure the content of crystal water, and calculate the corresponding hydration rate.

[0062] Example 3

[0063] A process for rapid hydration of anhydrous gypsum comprises the following steps:

[0064] S1. Grind 50g of anhydrous gypsum to a specific surface area of ​​520m 2 / kg, obtain powdered anhydrous salt gypsum for use;

[0065] S2, 30g of the powdered anhydrous gypsum of step S1, 7.5g of dihydrate gypsum seed, 1.8g of calcined alum, 0.15g of composite surfactant, 0.042g of melamine-based water reducer and 200ml of deionized water were mixed, and stirred at 25°C for 23h to obtain a hydrated slurry for standby use, wherein the composite surfactant is a mixture of modified lignin-based surfactant A and tristyrylphenol polyoxyethylene ether phosphate monoester, and the mass ratio is 1:0.12;

[0066] S3. Add 50 ml of anhydrous ethanol to the hydrated slurry in step S2, filter with suction, wash with anhydrous ethanol three times, dry at 45° C. to constant weight, measure the content of crystal water, and calculate the corresponding hydration rate.

[0067] Example 4

[0068] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that the mass of the composite surfactant in step S2 is 0.05 g.

[0069] Example 5

[0070] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that the mass of the composite surfactant in step S2 is 0.3 g.

[0071] Example 6

[0072] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that in step S2, the mass ratio of the modified lignin-based surfactant to the tristyrylphenol polyoxyethylene ether phosphate monoester in the composite surfactant is 1:0.05.

[0073] Example 7

[0074] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that the modified lignin-based surfactant A is replaced by the modified lignin-based surfactant B in equal amounts.

[0075] Example 8

[0076] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that the modified lignin-based surfactant A is replaced by the modified lignin-based surfactant C in equal amounts.

[0077] Comparative Example 1

[0078] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that the modified lignin-based surfactant A is replaced by an equal amount of sodium lignin sulfonate.

[0079] Comparative Example 2

[0080] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that the modified lignin-based surfactant A replaces the composite surfactant in equal amounts.

[0081] Comparative Example 3

[0082] The present invention provides a process for rapid hydration of anhydrous salt gypsum. The specific implementation method is the same as that of Example 1, except that tristyrylphenol polyoxyethylene ether phosphate monoester is used to replace the composite surfactant in equal amounts.

[0083] Performance Testing

[0084] The hydration rates of the anhydrous gypsum rapid hydration processes of the above-mentioned Examples 1-8 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.

[0085] The crystal water is measured according to GB / T 17669.2-1999 "Determination of the crystal water content of building gypsum". The hydration rate is the percentage of anhydrous salt gypsum hydrated into dihydrate gypsum in the total amount of ground powdered anhydrous salt gypsum.

[0086] Table 1

[0087]

[0088] It can be seen from the data in Table 1 that the process of anhydrous salt gypsum hydration in Examples 1-3 of the present invention has the characteristics of high hydration rate as a whole. Among them, Examples 4-6 respectively change the addition ratio of the composite surfactant in step S2 and the composite ratio of the modified lignin-based surfactant and tristyrylphenol polyoxyethylene ether phosphate monoester in the composite surfactant, so that the synergistic effect between the composite surfactant and the hydration promoter and the water reducer and the composite surfactant decreases, resulting in a decrease in hydration rate; Examples 7-8 change the modification ratio of methyl allyl polyoxyethylene ether and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine to sodium lignin sulfonate in the modified lignin-based surfactant, so that the dispersibility of sodium lignin sulfonate is not effectively improved, thereby showing a phenomenon of decreased hydration rate; Comparative Examples 1-3 are sodium lignin sulfonate instead of modified lignin-based surfactant A and modified lignin-based surfactant A and tristyrylphenol polyoxyethylene ether phosphate monoester respectively replace the composite surfactant, and the test finds that the hydration rate of the process of anhydrous salt gypsum hydration shows poor results.

[0089] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for rapid hydration of anhydrous gypsum, characterized in that: The following steps are involved: S1. Grind the anhydrous gypsum to a specific surface area of ​​480-520m 2 / kg, obtain powdered anhydrous salt gypsum for use; S2, mixing the powdered anhydrous salt gypsum, dihydrate gypsum seed, hydration promoter, composite surfactant, water reducer and deionized water of step S1, stirring at 15-25° C. for 23-25 ​​hours to obtain a hydrated slurry for standby use, wherein the composite surfactant is a mixture of modified lignin-based surfactant and tristyrylphenol polyoxyethylene ether phosphate monoester; S3, adding anhydrous ethanol to the hydrated slurry in step S2, filtering, washing, and drying to constant weight to obtain dihydrate gypsum; The method for preparing the modified lignin-based surfactant in step S2 comprises the following steps: (1) Add sodium lignin sulfonate to deionized water, introduce inert gas, heat to 45-55°C, stir for 15-25 minutes, add potassium persulfate, stir for 20-40 minutes, heat to 70-80°C, add methyl allyl polyoxyethylene ether, stir for 3-4 hours, add isopropanol, purify, dry, grind, and obtain the product for use; (2) Add the product of step (1) into deionized water, add sodium hydroxide aqueous solution to adjust the pH to 10-12, add N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, stir at 65-75° C. for 10-20 min, add formaldehyde aqueous solution, heat to 80-90° C., react for 3-4 h, cool to room temperature, add anhydrous ethanol, take the solid, wash, and dry to obtain a modified lignin-based surfactant.

2. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: The mass ratio of the powdered anhydrous gypsum to the dihydrate gypsum seed crystals in step S2 is 1:(0.15-0.25).

3. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: Step S2 The mass ratio of powdered anhydrous gypsum, hydration promoter, composite surfactant and water reducing agent is 1: (0.04-0.06): (0.003-0.005): (0.001-0.0014).

4. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: The hydration promoting agent in step S2 is calcined alum.

5. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: The mass ratio of the modified lignin-based surfactant to tristyrylphenol polyoxyethylene ether phosphate monoester in the composite surfactant in step S2 is 1:(0.08-0.12).

6. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: In the step (1), the mass ratio of sodium lignin sulfonate to methyl allyl polyoxyethylene ether is 1:(0.5-0.7).

7. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: In the step (2), the mass ratio of the product to N-butyl-2,2,6,6-tetramethyl-4-piperidinamine is 1:(0.1-0.3).

8. The process for rapid hydration of anhydrous gypsum according to claim 1, characterized in that: The water reducing agent in step S2 is a melamine-based water reducing agent.

9. The process for rapid hydration of anhydrous gypsum according to any one of claims 1 to 8, characterized in that: The hydration rate is not less than 93%.

Citation Information

Patent Citations

  • Activator for rapid hydration of type II anhydrous gypsum and rapid hydration method

    CN110128045A

  • Process for continuous modification of dihydrate gypsum and modified dihydrate gypsum obtained by the process

    CA2731836A1

  • Method for producing building material with low-temperature ceramic modified industry by-product gypsum

    CN101314530A